(untitled) (Global Journal of Medical Research, 2020)
Brevundimonas vesicularis, a non-fermenting gram-negative bacterium, has rarely been diagnosed as a cause of infection in an otherwise healthy child. In this report, we describe Brevundimonas vesicularis bacteremia, in an 8 months old healthy girl who was treated successfully with intravenous piperacillin-tazobactam.